Empowered or disempowered? The role of national parliaments during the reform of European economic governance - Aleksandra Maatsch (Max Planck Institute for the Study of Societies, 2015)
This paper investigates how the intergovernmental reform process of European economic governance affected national parliaments' oversight of that policy area. Which parliaments became disempowered and which managed to secure their formal powers - and why? The dependent variable of the study is operationalized as the presence or absence of "emergency legislation" allowing governments to accelerate the legislative process and minimize the risk of a default by constraining national parliaments' powers. This paper examines how national parliaments in all euro-zone states were involved in approving the following measures: the EFSF (establishment and increase of budgetary capacity), the ESM and the Fiscal Compact. The findings demonstrate that whereas northern European parliaments' powers were secured (or in some cases even fostered), southern European parliaments were disempowered due to the following factors: (i) domestic constitutional set-up permitting emergency legislation, (ii) national supreme or constitutional courts' consent to extensive application of emergency legislation and (iii) international economic and political pressure on governments to prevent default of the legislative process. Due to significant power asymmetries national parliaments remained de jure but not de facto equal in the exercise of their control powers at the EU level. As a consequence, both the disempowerment of particular parliaments and the asymmetry of powers among them had a negative effect on the legitimacy of European economic governance. – – Das Discussion Paper untersucht, wie sich der zwischenstaatliche Prozess zur Reform der wirtschaftspolitischen Steuerung in der Europäischen Union auf die Aufsichtskompetenzen der nationalen Parlamente über diesen Politikbereich ausgewirkt hat. Welche Parlamente wurden entmachtet, und welchen gelang es, ihre formellen Kompetenzen zu wahren - und warum? Bei dieser Untersuchung wird die abhängige Variable als das Vorhandensein oder Fehlen einer Möglichkeit zur "Notstandsgesetzgebung" operationalisiert, die es Regierungen erlaubt, das Gesetzgebungsverfahren zu beschleunigen und das Risiko des Scheiterns eines Gesetzentwurfs zu minimieren, indem sie die Kompetenzen der nationalen Parlamente einschränkt. Dieser Beitrag analysiert, wie die nationalen Parlamente aller Staaten des Euroraums eingebunden waren, um folgende Maßnahmen zu genehmigen: die Europäische Finanzstabilisierungsfazilität EFSF (Einrichtung und Aufstockung), den Europäischen Stabilitätsmechanismus ESM und den Europäischen Fiskalpakt. Die Ergebnisse zeigen, dass die Kompetenzen der Parlamente im nördlichen Europa gewahrt (und in einigen Fällen sogar gestärkt) wurden, wohingegen die Parlamente Südeuropas aufgrund der folgenden Faktoren entmachtet wurden: (i) Nationale Verfassungsordnung, die eine Notstandsgesetzgebung erlaubt, (ii) nationale oberste Gerichte oder Verfassungsgerichte, die der extensiven Anwendung einer Notstandsgesetzgebung zustimmen, und (iii) internationaler wirtschaftlicher und politischer Druck auf Regierungen, um ein Scheitern eines Gesetzentwurfs im Gesetzgebungsverfahren zu vermeiden. Die nationalen Parlamente blieben bei der Ausübung ihrer Kontrollkompetenzen auf EU-Ebene zwar formalrechtlich einander gleichgestellt, faktisch waren sie es aufgrund erheblicher Machtasymmetrien jedoch nicht. Somit hatte sowohl die Entmachtung einzelner Parlamente als auch die Asymmetrie der Kompetenzen zwischen Parlamenten einen negativen Effekt auf die Legitimität der wirtschaftspolitischen Steuerung in der Europäischen Union.
Keywords: 300